Bacteriophages and dairy fermentations - Briggiler Marcó, Mariángeles (2014)
This review highlights the main strategies available to control phage infection during large-scale milk fermentation by lactic acid bacteria. The topics that are emphasized include the factors influencing bacterial activities, the sources of phage contamination, the methods available to detect and quantify phages, as well as practical solutions to limit phage dispersion through an adapted factory design, the control of air flow, the use of adequate sanitizers, the restricted used of recycled products, and the selection and growth of bacterial cultures.